The effect of income distribution and fiscal policy on growth, investment, and budget balance: the case of Europe - Thomas Obst; Özlem Onaran; Maria Nikolaidi (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
This paper develops a multi-country post-Kaleckian demand-led growth model that incorporates the role of the government. One novelty of this paper is to integrate crosscountry effects of both changes in income distribution and fiscal policy. The model is used to estimate econometrically the effects of income distribution and fiscal policy on the components of aggregate demand in EU15 countries. The results show that a policy mix that combines the simultaneous implementation of a pro-labour wage policy, an expansionary fiscal policy and a progressive tax policy in all EU countries leads to a significant rise in the EU15 GDP. The impact of wage policies is positive but small; the overall stimulus becomes much stronger with fiscal expansion. This policy mix leads to an improvement in the budget balance in all the EU15 countries, suggesting that expansionary fiscal policy is sustainable when it is combined with wage and progressive tax policy.
Keywords: E12; E22; E25; E62; 330; Wage Share; Growth; European Multiplier; Demand Regime; Fiscal Policy